Green Entrepreneurship and Eco-Innovation in Technology-Driven Ventures - Maan, Happy; Sandhu, Harleen (Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems; Vol 1 No 1 (2025): Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems, 2025)
Green entrepreneurship and eco-innovation play a crucial role in responding to the increasingly urgent environmental challenges, while fostering economic growth and sustainability in technology-driven sectors. With their ability to scale, influence industries, and drive systemic change, technology ventures are uniquely positioned to develop solutions that address global sustainability issues, including climate change, resource depletion, and pollution. This review article provides a comprehensive exploration of green entrepreneurship and eco-innovation, focusing on how these practices are shaping the future of technology-based businesses. The review examines the primary drivers of green entrepreneurship, such as environmental concerns, consumer demand for sustainable products, regulatory pressures, and the profitability of green business models. It highlights the transformative potential of technology in advancing eco-innovation through product, process, and business model innovations that promote environmental sustainability. The article further explores the barriers and challenges that entrepreneurs face in pursuing green ventures, including access to funding, market uncertainties, and technological complexities. Additionally, the paper delves into the strategic frameworks and policies that support the integration of sustainability into the tech industry. It discusses the role of government policies, public-private partnerships, and innovation ecosystems in fostering an environment conducive to green entrepreneurship. It also outlines the importance of building supportive networks, developing green financing mechanisms, and encouraging collaboration between startups, research institutions, and policy-makers. Finally, the review provides recommendations for entrepreneurs and policymakers to accelerate the green transition in the technology sector. Entrepreneurs are encouraged to embrace sustainability as a core value, innovate across business processes, and collaborate with key stakeholders to scale up their green solutions. Policymakers are urged to create more robust frameworks that incentivize eco-innovation and provide the necessary resources for startups to thrive. The article concludes by stressing the long-term importance of adopting sustainable business practices in the technology sector, emphasizing that eco-innovation not only addresses global environmental concerns but also positions businesses for continued success in a competitive, environmentally-conscious market.